The significance of physical activity and mental health among people aged 60 and over (Training and Practice : Journal of Educational Sciences, 2018)
The number and ratio of retired age population reveals an increasing tendency all over theworld. A pensioner in the 21st century will be able to plan ahead not only for 5-10 years but fora longer period of time. In many cases, longer life expectancy is accompanied by a sedentarylifestyle that may contribute to the emergence of several diseases, including cardiovasculardiseases or musculoskeletal disorders in leading position. Regular physical and mental activitymanifests itself as a significant factor of prevention that can decelerate physical and mentaldeterioration to a great extent. In addition to physical activity, healthy nutritional habits, theactive use of leisure time, mental health and improving intellectual skills, as major componentsof a healthy lifestyle, are able to have a positive impact on the process of ageing, improvementsin the quality of life, achieving a healthy level of fitness. In this study we want to highlight thoseactivities that are able to support the key factors of maintaining and developing mental health,mental and physical activity and healthy nutritional habits, thus providing a meaningful,healthy lifestyle over the age of 60.